PARylation of HMGA1 desensitizes esophageal squamous cell carcinoma to olaparib - Xin‐Yuan Lei; Kai‐Yue He; Qiu‐Tong Li; Lei Zhang; Dan‐Hui Wu; Jing‐Yu Yang; Jin‐Rong Guo; Meng‐Jie Liu; Zi‐Long Zhao; Jun‐Qi Li; Huai Liu; Yuan Zhao; et al. (Clinical and Translational Medicine)
Abstract As a chromatin remodelling factor, high mobility group A1 (HMGA1) plays various roles in both physiological and pathological conditions. However, its role in DNA damage response and DNA damage‐based chemotherapy remains largely unexplored. In this study, we report the poly ADP‐ribosylation (PARylation) of HMGA1 during DNA damage, leading to desensitization of esophageal squamous cell carcinoma (ESCC) cells to the poly(ADP‐ribose) polymerase 1 (PARP1) inhibitor, olaparib. We found that HMGA1 accumulates at sites of DNA damage, where it interacts with PARP1 and undergoes PARylation at residues E47 and E50 in its conserved AT‐hook domain. This modification enhances the accumulation of Ku70/Ku80 at the site of DNA damage and activates the DNA‐dependent protein kinase catalytic subunit, facilitating nonhomologous end‐joining repair. In both subcutaneous tumour models and genetically engineered mouse models of in situ esophageal cancer, HMGA1 interference increased tumour sensitivity to olaparib. Moreover, HMGA1 was highly expressed in ESCC tissues and positively correlated with PARP1 levels as well as poor prognosis in ESCC patients. Taken together, these findings reveal a mechanistic link between HMGA1 and PARP1 in regulating cell responses to DNA damage and suggest that targeting HMGA1 could be a promising strategy to increase cancer cell sensitivity to olaparib.